2018
DOI: 10.1108/ijge-10-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between women’s presence in corporate positions and firm performance

Abstract: Purpose The purpose of this paper is to analyze, in the Colombian developing context, the relationship between the presence of women in corporate positions and the financial performance of the company and to know if there are differences between family and non-family firms. Design/methodology/approach Building on the contingency theory of leadership, which emphasizes that leader’s personality and the situation in which that leader operates influences corporate decision-making, the authors use panel data mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…Accordingly, the above scholars concluded that there was no association between the aforesaid two variables. However, a positive relationship between the variables was found in one study which was based on the ROA ratio measure [13]. Similar results were obtained in a study carried out on 112 US companies [43].…”
Section: Independent Variable-female Representation Within Boardroomssupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly, the above scholars concluded that there was no association between the aforesaid two variables. However, a positive relationship between the variables was found in one study which was based on the ROA ratio measure [13]. Similar results were obtained in a study carried out on 112 US companies [43].…”
Section: Independent Variable-female Representation Within Boardroomssupporting
confidence: 81%
“…The ROA has been used as an accounting based measurement of firm financial performance in terms of profitability. ROA has been used in most previous studies which have focused on the relationship between females employed at the decision making level and firm financial performance [5,7,[11][12][13][14].…”
Section: Return On Assetsmentioning
confidence: 99%
“…A diversified board might provide diverse perspectives and points of view as a means of enriching the strategic role of the board, and overcome risk-averse tendencies [52] that could jeopardize innovation. Gender is one of these characteristics related to the board composition, in which diversity could be translated into better governance [60]. It is also a topic that has recently been widely discussed because increasing the representation of women in the upper corporate echelons is considered a matter of social sustainability, entailing social justice and equity, and avoiding the restrictions on women occupying highly responsibility positions in companies.…”
Section: Discussionmentioning
confidence: 99%
“…Since IPO firms have to manage the perceptions of potential investors and at the same time signal their good quality, the hypothesis which stands to be tested is whether the presence of female directors has any contribution in mitigating information asymmetry and ultimately checking the underpricing. Although several studies can be found that examine the impact of female directors on performance of firm, for example, a recent one by Moreno-Gómez and Calleja-Blanco (2018) conducted in Colombia found a positive association between the two. Yet there is a dearth of research examining the impact of female directors on underpricing of IPOs, that is, the aim here is to see how market reacts to a female presence on the board.…”
Section: Review Of Literaturementioning
confidence: 99%